Prevalen hipertensi di kalangan penduduk berumur 21 tahun ke atas di Felda Bukit Cerakah, 1993. - Anita Y.,; Dayang Anita A.A.,; Fadzullah A.,; Hasri H.,; Khairil Aswad O.,; Khaw H.H.,; Lee W.T.,; Mak C.S.,; Marina M.S.,; Mohamad Sabry L.,; Mohd Hudzairy A.,; Mohd Rapi A.R.,; et al. (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 1994)
A cross-sectional study was conducted in FELDA Bukit Cherakah 1 and 2, Mukim Jeram, District of Kuala Selangor from July -August 1993. The purpose of this study is to determine the prevalence of hypertension among residents aged 21 years and above, and its association with factors such as age, sex, obesity, educational status, family income, family history of hypertension, smoking, Diabetes Mellitus, knowledge on hypertension, sodium intake and physical activities. A total of 128 respondents were selested through random sampling using the Fischer Random Table. Data were collected through guided-interview questionnaire, sphygmomanometer for blood pressure measurements, anthropometric measurements and urine nicotin test. The study found that the prevalence of hypertension associations between hypertwnsion and age, knowledge of hypertension and obesity.